PEMBANGUNAN BERWAWASAN KEPENDUDUKAN KONSEP DAN KEMUNGKINAN IMPLEMENTASINYA - Murjana Yasa, I G W (PIRAMIDA; Vol. 1, No. 1 April 2005)
Development with demography perspective put population as the central point of development, i.e population as both object and subject of development. In the autonomy era which focus on participative development pattern and put local wisdom in the front is fit the paradigm of development with demography perspective. However, there is a question emerge related to implementation of paradigm of development with demography perspective with respect to economic and social condition of Balinese community. Analysis is done based on published secondary data related to economic and social condition of Bali population such as income and income differences among areas, prosperity level, population distribution among areas, shifting of population composition according to ethnicity, and tendency of unemployment rate. Based on the analysis the solution is recommended related to an effort of mainstreaming paradigm of development with demography perspective. The result shows that the great differences of population per capita income between Northern part and Eastern part of Bali development areas, and Southern part of Bali development areas reflects that several population problems has not been integrated properly in development planning. Indication of such an imbalance is also pictured from the size and percentage of poor population, population density, and also unemployment rate. There is a tendency that the high unemployment rate is direct to population mobility pattern. Population mobility flows original from northern and eastern part of Bali development areas (especially Buleleng and Karangasem regencies), experience relatively high unemployment rate, so does Southern part of Bali development area. Improvement of implementation of development with demography perspective requires importance of population data quality improvement. Musrenbang can become an enhancement of participative development planning from the bottom and put local wisdom in the front.
Keywords: demography perspective, paradigms of development, population problem